FACTORS CONTRIBUTING TO THE RECOVERY FROM ANEMIA IN HEMODIALYSIS PATIENTS DURING THE ADMINISTRATION OF RECOMBITANT ERYTHROPOIETIN - Boljevic, Tanja; Pelicic, Damir (HEALTH CARE, 2022)
Introduction/Aims: Anemia is the commonest complication in patients on a chronic hemodialysis program and is the cause of reduced quality of life. The aim of this study was to identify the factors that contribute to the better control of anemia with the help of recombinant erythropoietin in persons undergoing hemodialysis.Methods: The cross-sectional study was conducted in 2017 and it included 52 persons on hemodialysis at the Clinical Center of Montenegro. The participants were divided into those, in whom hemoglobin values increased to satisfactory values (110 g/l or more) after three months of application of recombinant erythropoietin (group 1), and those, in whom hemoglobin values were lower than 110 g/l (group 2). Data were collected from the medical history of all participants. T-test was used for the statistical analysis of data.Results: After the three-month administration of erythropoietin, the target value of hemoglobin of 110 g/l or more (group 1) was achieved in only 21 patients (40.4%), while hemoglobin values were below 110 g/l in 59.6% of patients. Participants, in whom target values of hemoglobin were not achieved, received significantly higher average doses of erythropoietin and they had higher body mass index in comparison to participants, in whom the target values were achieved. There was no significant difference between the examined groups regarding the response to erythropoietin, duration of erythropoietin therapy, duration of hemodialysis, participants’ age, skin-fold thickness, upper arm width, transferrin values, number of erythrocytes, value of albumin, hemoglobin, hematocrit and iron.Conclusion: Possible factors that contribute to worse control of anemia are higher doses of erythropoietin and greater level of nutritional status estimated according to the body mass index. Further research is necessary aimed at finding factors that would contribute to the elimination of anemia in persons on hemodialysis, because non-treated anemia may lead to numerous unfavorable outcomes (poor quality of life, cardiovascular diseases, cerebrovascular insult, decreased survival rate etc.).
Keywords: hemodialysis, erythropoietin, chronic kidney insufficiency